Agricultural products to implement home gardens in Altos de Cazucá, Soacha (2018)
The Loma Linda of Altos de Cazucá neighborhood (Soacha, Cundinamarca) is affected by forced displacement, which increases both the misery belts and the malnutrition problems of the municipality. A potential way to mitigate these issues is the introduction of sustainable agriculture methods such as urban agriculture (UA), which contributes to produce vegetal crops that favor the alimentary and nutritional sovereignty. Knowing the consumption habits of the community is necessary to implement different UA establishment and production methods. Therefore, to identify the main consumed agricultural products in the Loma Linda of Altos de Cazucá neighborhood and select those that can be implemented in a family garden under an UA model, we used a semi-formal interview tool. We found that peas and carrots are the most consumed with 90% and 86%, respectively, and that quinoa is the least consumed with 8%. Among aromatics and spices, the most consumed are spearmint, aloe, and lemongrass, with percentages that range from 58 to 48. Additionally, 26% of the polled population expressed having full and average knowledge in subjects of UA; 38%, having average knowledge, and 36% admitted having no information in this regard, however 98% declared to be willing to participate in UA activities.